Seleksi Sub-Kontraktor Proyek Konstruksi Jalan Layang - Hery Muhendra; Sawarni Hasibuan (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
The aim of the study is to measure the selection criteria of sub-contractor fly over construction project and to level the sub-contractors based on five criteria which are financial factor, practical factor, managerial, safety, and company’s image. The right sub-contractor as partner is the important factor for main contractor in building the fly over based on the schedule and the budget with good quality. The study was using ANP (analytic network process) to evaluate the criteria interrelation of main contractor when making decisions of uncertainty situation to be better. The subject of the study is the Tendean-Blok M-Cileduk fly over construction project. The result shows that sub-contractor A has the highest result of 0.4798, sub-contractor B with 0.3646 and the last is sub-contractor C with 0.1556.